THE EFFECTIVENESS OF QUIZIZZ IN STUDENTS’ VOCABULARY MASTERY OF ELEVENTH GRADE AT SMAN 1 GROGOL - Fadhilah, Lutfiana Dwi Nur; Anggrisia, Nur Fitria (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The objective of the study was to determine whether the use of Quizizz was effective or not for students’ vocabulary mastery of eleventh grade at SMAN 1 Grogol. This study used quasi-experimental design. The subject of this study was XI Social 2 and XI Social 3 of SMAN 1 Grogol. The vocabulary learned is receptive and productive vocabulary in explanation text. The data was obtained by conducting a post-test. The results showed a difference in post-test results between the experimental and control groups. The average score of the experiment group was 59.44, while the control group was smaller at 47.48. The results obtained from the statistical test show that the significance value (Sig. 2-tailed) is 0.004, where the value obtained is <0.05. This indicates that Ha is accepted and H0 is rejected. It can be concluded that Quizizz is effective in learning receptive and productive vocabulary mastery of explanation text in eleventh grade.